“Dr. Google” consultation and health anxiety among primary healthcare patients: The mediation effect of health literacy - Eddieson Pasay-an; Reem Humaidi Alalawi; Sumathi Robert Shanmugam; Salman Amish Alshammari; Maha Sanat Alreshidi; Sameer Alkubati; Nojoud Alrashidi; Petelyne Pangket; Lizy Sonia Benjamin; Ferdinand Gonzales; Lailani Sacgaca; Romeo Mostoles Jr (PLoS ONE, 2025)
Background Promoting health literacy is a successful intervention for cyberchondriasis and health anxiety. However, no study has examined how cyberchondria, health anxiety, and health literacy are interrelated. Objective This study aimed to determine the prevalence of cyberchondria among primary healthcare patients in Saudi Arabia and examine the relationship between cyberchondria and health anxiety and the mediating role of health literacy in this relationship. Methods This cross-sectional study involved 422 participants from all over Saudi Arabia’s five regions, specifically from primary healthcare centers. Data were collected between August 1, 2024 to September 1, 2024. Results Age, sex, marital status, nationality, region, place of residence, social media use, and Internet use were significantly associated with cyberchondria health literacy and health anxiety (p < 0.001). Structural equation modeling (SEM) revealed that cyberchondria had a positive effect on both health literacy and health anxiety (p < 0.001). Additionally, regarding the age group 65 years or older, for example, results indicate that in accordance with most previous studies reviewed here, cyberchondria can predict higher levels of health anxiety in people who have low levels of education. Conclusions Cyberchondria is interrelated with other variables such as demographic characteristics and behavioral patterns. They highlighted the significance of interventions directed at enhancing health literacy to curtail cyberchondria and reduce health anxiety. The present findings suggest that cyberchondria manifests in many different ways, making it a complex phenomenon. It also helps us to understand how the patient may become an active partner rather than a passive recipient in his/her own care.